(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study highlights false conceptions related to policing as a profession for women and highlights reasons for labeling this profession as not suitable for women. The study challenges the fact that regardless of active participation of women in every sector, women are still facing stereotypical behavior from society due to their career building in policing. Through qualitative approach, the study unravels different patterns of behavior. Phenomenological design was used as a strategy of inquiry. Ten women police officers were selected using purposive and snowballing sampling techniques. A descriptive design of interview guide is used to explore and evaluate different aspects related to the research study. The theoretical lens of labeling theory and social learning theory were used to analyze results. Findings of this study show that major factors behind low participation of women in policing and reasons of labeling this profession as inappropriate for females include issues of acceptance from society and non-suitable working environment of policing for women. The participants of the study have shown their progressive concern towards profession of policing by sharing their efforts towards contribution in their profession and showing their concerns towards the importance of inclusion of women in policing and its positive aspects.